IMPLEMENTATION OF DIGITAL MARKETING FOR MSMES IN GEDANGAN DISTRICT - Hikmah , Kharisma Nur; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of digital marketing in MSMEs in Gedangan District by adopting the policy implementation theory model from George C. Edward III. Method: The approach used is qualitative descriptive, involving in-depth interviews, direct observation in the field, and document data collection. Results: The results of the study show that the use of digital marketing has resulted in an increase in revenue and the expansion of the small and medium enterprises (MSMEs) market. However, implementation still faces many challenges. This includes elderly business actors who do not have digital literacy, lack of technological infrastructure, and lack of post-training mentoring. Although policy communication has been carried out through socialization and training, it has not been consistent and equitable. While most senior business actors stick to conventional approaches, young human resources tend to be more flexible in social media management. Novelty: For continuous improvement, consistent implementation of digital marketing, more practical routine training and assistance are needed. In addition, it is necessary to increase access to financing and improve technological infrastructure so that MSME actors can maximize promotion and market expansion in a sustainable manner.